Innovative online learning in entrepreneurship education: The impact of embedding real-life industry practice in the virtual learning environment. Issue 6 (December 2022) - Oliver, Paul G; Oliver, Stanley
Applied areas of entrepreneurship are growing in popularity due to the ongoing need for students to gain specialised skills to find employment after graduation. This study explores how educational scaffolding can facilitate the delivery of online experiential activities to improve the entrepreneurial learning experience and the performance of music management students by using information and communications technology tools within the virtual learning environment. A case study methodology was adopted to present two scenarios of innovative online learning delivered in a postgraduate programme in music management. This research takes into consideration the difficult transitional journey for some students from studying to being immediately thrust into the workplace, which often requires different types of knowledge, experience, skills and competences. The findings show that, by strengthening industry links, tutors can build a portfolio of online practical activities that represent the 'real-life' industry, helping to forge long-term, collaborative partnerships to facilitate learners' acquisition of more meaningful knowledge and opportunities.